Synthesis and pharmacological activity of various organic and inorganic salts of phenyl derivatives of imidazobenzimidazole - Olga N. Zhukovskaya; Natalya V. Eliseeva; Pavel M. Vassiliev; Gleb V. Pridvorov; Olesya Yu. Grechko; Anatoly S. Morkovnik; Alexander A. Spasov (Belgorod National Research University, 2024)
Introduction: The creation of new opioid analgesics that are devoid of the main undesirable effects - euphoria, respiratory depression, tolerance - is an important task for the treatment of pain syndrome. Eighteen salts of 9-pyrrolidinoethyl-(1a), 9-piperidinoethyl-(1b), and 9-morpholinoethyl-2-(4-fluorophenyl)benzo[d]imidazo[1,2-a]imidazole (1c) were synthesized and tested for kappa agonist and analgesic activity. Materials and Methods: Specific analgesic activity studies were conducted using models of nociceptive pain in the "Hot/Cold-plate" and "Plantar Test" tests, and in neuropathic pain against the background of sciatic nerve ligation. The relationship between the physicochemical and pharmacological properties of the compounds was studied in silico using quantum chemistry methods and artificial neural network technology. Results: The most active compound identified was 4-(2-(2-(4-fluorophenyl)-benzo[d]imidazo[1,2-a]imidazol-9-yl)ethyl)morpholine dihydrochloride (1c.2HCl). EC50, acute toxicity, and conditional therapeutic index values were calculated, which were 38.8 times superior to the kappa agonist U50488. It was established that compound 1c.2HCl exhibits a dose-dependent analgesic effect in the "Hot/Cold-plate" test, which is six times superior to that of butorphanol, maintaining a statistically significant effect for six hours in the "Plantar test" and without causing the formation of tolerance with a ten-day administration. In models of neuropathic pain syndrome, 1c.2HCl with a fourteen-day administration significantly reduced tactile and cold allodynia by three and 1.6 times, respectively, and was not inferior in activity to gabapentin. The kappa-opioidergic mechanism of the antinociceptive action of 1c.2HCl compound was confirmed. Quantum chemistry methods and artificial neural network technologies have shown that the high level of kappa-opioid agonist activity of hydrochlorides, in contrast to other salts, results in lower total energy production; therefore, there is a significant increase in energy during the formation of a salt supramolecular complex. Conclusion: The most active compound was identified - 1c.2HCl, for which kappa-opioid activity in vitro and analgesic properties were revealed in various in vivo models. It has been shown that the compound does not cause the formation of tolerance and is not toxic.